IMPLEMENTASI KOMPETENSI SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KEPROFESIAN BERKELANJUTAN DI SD NEGERI 1 BATI-BATI - Hadani; Rahman, Arif; Sakka, Ambo; Metroyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the implementation of the principal’s supervisory competence in enhancing teachers’ continuous professional development (CPD) at SD Negeri 1 Bati-bati. This research employed a qualitative approach with a case study design. The research subjects included the principal and teachers selected through purposive sampling. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings reveal that the implementation of supervisory competence covers planning, implementation, feedback, and follow-up integrated with CPD. The supervision process is carried out through a combination of planned and unannounced supervision to obtain authentic classroom practices. Feedback is provided constructively and followed by clinical supervision as a form of professional guidance. In addition, supervision is integrated with CPD through training rotation, documentation, and dissemination of training outcomes. However, several challenges remain, such as the lack of structured follow-up and limited technological competence among some teachers. This study concludes that the principal’s supervisory competence plays a significant role in improving teachers’ professional development sustainably.